THE OSMIUM RIVERINE FLUX AND THE OCEANIC MASS BALANCE OF OSMIUM - Levasseur S.; Birck J.L.; Allegre C.J. (My University, 1999)
The osmium concentration ([Os]) and isotopic composition were determined in a set of 17 of the largest rivers of the world. [Os] varies between 4.6 and 52.1 pg/kg and the 187Os/188Os ratio varies between 0.64 and 2.94. Measurement of rainwater samples shows that there is no input of oceanic Os to the continent through rain. Assuming a negligible anthropogenic Os input in the dissolved load, the natural average river water has an Os concentration of 7.9 pg/kg and a mean 187Os/188Os ratio of 1.54. The total riverine flux of Os to the ocean is estimated to be 295 kg/yr. The dissolved Os flux from island arcs and oceanic islands represents less than 5% of the total riverine flux and is not further considered. The continental Os flux to the ocean is then represented by the riverine flux, as dissolved Os from eolian dust and glacial sediments is negligible. Assuming steady state, it is possible to estimate a maximum unradiogenic flux to the ocean of 126 kg/yr (cosmic dust or mantle-derived) and an oceanic residence time between 2.5x104 and 5.4x104 with a mean of 3.5x104 year. The estimation of the flux of dissolved cosmic particles shows that their contribution to the seawater Os would be ~14% of the contribution of the unradiogenic component, which means that the mantle-derived flux should contribute a major part. The first results on water from high temperature axial hydrothermal systems indicate that their input is probably negligible, which would necessitate that dominant contribution from the low temperature alteration of the oceanic crust and/or of the ultramafic exposures contributes dominantly to the input of unradiogenic Os to the seawater. We show that it would be necessary to leach 1.3% of the Os contained in the volume of ultramafic exposures accessible to seawater to account for all of the unradiogenic component contribution. Another simpler but less likely possibility is that the dissolved cosmic dust represents the only source of dissolved unradiogenic Os to the ocean in which case the riverine input represents 94% of the total dissolved flux to the ocean instead of 70%. The modern global dissolved Os flux to the ocean would then have a 187Os/188Os ratio of 1.44 instead of 1.06 and the system would be far from steady state.
Keywords: OSMIUM; STREAM TRANSPORT; FLUVIAL ENVIRONMENT; WORLD OCEAN; ISOTOPES; MASS BALANCE